On the benefits of repaying - Francesca Caselli; Matilde Faralli; Paolo Manasse; Ugo Panizza (Graduate Institute of International and Development Studies, 2021)
This paper studies whether countries benefit from servicing their debts during times of widespread sovereign defaults. Colombia is typically regarded as the only large Latin American country that did not default in the 1980s. Using archival research and formal econometric estimates of Colombia's probability of default, we show that in the early 1980s Colombia's fundamentals were not significantly different from those of the Latin American countries that defaulted on their debts. We also document that the different path chosen by Colombia was due to the authorities' belief that maintaining a good reputation in the international capital market would have substantial long-term payoffs. We show that the case of Colombia is more complex than what it is commonly assumed. Although Colombia had to re-profile its debts, high-level political support from the US allowed Colombia to do so outside the standard framework of an IMF program. Our counterfactual analysis shows that in the short to medium run, Colombia benefited from avoiding an explicit default. Specifically, we find that GDP growth in the 1980s was higher than that of a counterfactual in which Colombia behaved like its neighboring countries. We also test whether Colombia's behavior in the 1980s led to long-term reputational benefits. Using an event study based on a large sudden stop, we find no evidence for such long-lasting reputational gains.
Keywords: F34; F32; H63; 330; Sovereign Debt; Default; Reputation